JUDICIAL CONSIDERATIONS IN THE CRIME OF ASSAULT (A STUDY OF DECISION NUMBER 327/PID.B/2024/PN SRH) - Darman Hasibuan; Syahrul Bakti Harahap (Jurnal Ilmu Hukum dan Keadilan, 2026)
Based on the research results, it shows that the legal provisions for criminal acts of assault based on the Criminal Code have been regulated in general for anyone who commits criminal acts of assault, namely Article 351 of the Criminal Code, Article 352, Article 351, Article 354, and Article 355. The punishment for the motorcycle gang who committed the crime of assault in the Sei Rampah District Court decision Number 327 / Pid.B / 2024 / PN Srh is appropriate if it refers to the article charged by the public prosecutor, namely Article 351 paragraph (1) of the Criminal Code. The judge's legal considerations in sentencing the motorcycle gang who committed assault based on decision number 327 are appropriate, namely proving the element of "whoever" using evidence of witness and defendant testimony that corresponds to the defendant's identity, proving the element of "intentionally committing assault" using evidence of witness testimony, victim, defendant, Visum et Repertum letter No. 287 / IV / RSUM / 2024.